An Empirical Study On The Output-Inflation Trade-Off In The Brics Countries - Sim, Chong Yang (Universiti Malaysia Sarawak (UNIMAS), 2013)
This study examines whether the short-run output-inflation trade-off in the BRICS countries follows the new Classical or new Keynesian theory. The variables used include inflation rate, nominal GDP and real GDP. The empirical model used is the Asai's (1999) version of BMR (1988) model. The Augmented Dickey-Fuller (ADP) unit root test, Autoregressive Conditional Heteroscedasticity (ARCH) test, and Generalized Autoregressive Conditional Heteroscedasticity (GARCH) test are employed in this study. Data published by the Datastream from the period of 2003:Ql to 2011:Q4 are utilized in this study. The empirical results show that the short-run output-inflation trade-off in Brazil, Russia and India are well reflected by the new Keynesian model, while the short-run output-inflation trade-off in South 8 4 Africa is well reflected by the new Classical theory. The short-run output-inflation trade-off in China followed neither the new Classical nor new Keynesian theory. Governments can utilize fiscal, monetary and inflation targeting policies in moderating business cycles in the case of Brazil, Russia and India. For the case of South Africa and China, governments are advised to intervene only when necessary.